2022
DOI: 10.1155/2022/4946197
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of FXYD2 Is Associated with Poor Prognosis and Increased Regulatory T Cell Infiltration in Clear Cell Renal Cell Carcinoma

Abstract: Background. FXYD2, a gene coding for the γ subunit of Na+/K+-ATPase, was demonstrated to involve in carcinogenesis recently. However, the specific role of FXYD2 in clear cell renal cell carcinoma (ccRCC) remains unknown. The current study was conducted to investigate the expression, biological function, and potentially immune-related mechanisms of FXYD2 in ccRCC. Materials and methods. The data from TCGA-KIRC, ICGC, GEO, Oncomine, ArrayExpress, TIMER, HPA datasets, and our clinical samples were used to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 89 publications
1
1
0
Order By: Relevance
“…Subsequently, the three immunomodulators most strongly correlated with NF-κB, namely Treg, CCR, and neutrophils, were selected for correlation analysis, and the results were all positively correlated, their correlation coefficients are 5.56, 0.60 and 0.51, respectively, all of them are statistically significant ( Figure 5B – 5D ). Previous studies have also shown that the activity of Treg, CCR and neutrophils is closely related to the occurrence and development of KIRC, which is consistent with the conclusion of our study [ 27 29 ].…”
Section: Resultssupporting
confidence: 93%
“…Subsequently, the three immunomodulators most strongly correlated with NF-κB, namely Treg, CCR, and neutrophils, were selected for correlation analysis, and the results were all positively correlated, their correlation coefficients are 5.56, 0.60 and 0.51, respectively, all of them are statistically significant ( Figure 5B – 5D ). Previous studies have also shown that the activity of Treg, CCR and neutrophils is closely related to the occurrence and development of KIRC, which is consistent with the conclusion of our study [ 27 29 ].…”
Section: Resultssupporting
confidence: 93%
“…Downregulation of FXYD2 is associated with poor prognosis in clear cell renal cell carcinoma. 39 Prevalence ratios (PR) of gallbladder disease are significantly higher for the Phenylalanine hydroxylase (PAH) deficiency cohort. 40 MPZL1 is highly expressed in advanced gallbladder carcinoma and promotes the aggressive behavior of human gallbladder carcinoma GBC-SD cells.…”
Section: Discussionmentioning
confidence: 99%